Pengembangan Media Pembelajaran Fisika Berbasis Glideapps dengan Model Problem-Based Learning Pada Materi Besaran dan Pengukuran Kelas X SMA - Hasna, Laeli Fauziyah; Ekawati, Elvin Yusliana; Pujayanto, Pujayanto (Universitas Negeri Surabaya, 2024)
This research aims to develop Glideapps-based physics learning media with a problem-based learning model on physical quantities and measurement material, as well as describing the results of the development of the learning media that has been prepared. The research used is Research and Development (R&D) with a 4D model which carries out three stages, namely Define, Design and Develop. The research data sources were two lecturers as experts, two class X physics teachers as reviewers, and 96 class X students at SMAN 8 Surakarta. Research data collection techniques use open and closed questionnaire methods. Data analysis was carried out quantitatively using criteria from Saifuddin Azwar. Based on the results of the analysis, the development of Glideapps-based physics learning media with a problem-based learning model on physical quantities and measurement material for class X SMA has very good criteria based on assessments from experts and reviewers. In the limited trial, 89% of students rated the physics learning media as having very good criteria and 11% as having good criteria. Meanwhile, in the field trials, as many as 90% of students rated the physics learning media as having very good criteria, 9% with good criteria, and 1% with sufficient criteria. The result of the development carried out is that the resulting physics learning media has 3 main pages, namely Home, Material and Evaluation. Media is accessed online using a smartphone/PC with a good and stable internet connection. The media can be operated without having to carry out the installation process first.